Comparative study on corrosion inhibition of N doped carbon dots for low alloy steel and aluminum alloy in HCl solution - Chunmiao Liu; Bin Wang; Xiaofang Peng; Yuxin Qin; Guanhui Gao; Jie Liu (Journal of Materials Research and Technology, 2025)
This study prepared N-doped carbon dots (N-CDs) as an inhibitor by employing citric acid and ethylenediamine as precursors via a hydrothermal method. The corrosion inhibition behavior of N-CDs on X65 steel and 7A04 aluminum alloy in HCl solution was systematically studied and compared using electrochemical measurements, weight loss test and surface analysis techniques. The results indicate that the synthesized N-CDs function as mixed-type inhibitors primarily inhibiting the anodic reaction, and they exhibit better corrosion inhibition performance on X65 steel compared to 7A04 aluminum alloy. The corrosion inhibition efficiencies of N-CDs increase and then decrease with concentration, and the extreme-value-phenomena of concentration appears at 100 mg/L, which is related to the stability and agglomeration degree of N-CDs in the solution. In addition, this study also compares and analyzes the corrosion inhibition mechanisms of N-CDs for both types of metals in HCl solution.